The design of non-invasive Functional Electrical Stimulation (FES) for restoration of muscle function - Azman, Amelia Wong; Naeem, Jannatul; Mohd Mustafah, Yasir (2012)
The idea of an FES is to stimulate the contraction of paralyzed muscles by inducing electrical pulses. Recent studies have demonstrated that the intervention of Functional Electrical Stimulation (FES) have improved patients with paralyzed muscle injuries. Unfortunately, due to the high cost of an FES device, rehabilitation centers in local hospitals are not equipped with FES devices. Generally, an FES device consists of electrodes and a stimulator. The stimulator of an FES device will act as the main controller that will provide with the activation or stimulation functions. This paper investigates the parameters that need to be addressed in designing an FES stimulator. While there are many different types of electrodes to be used in FES system, for this early work, we only look at FES systems application using only skin surface electrodes (non-invasive).